The Reliability And Accuracy Of Laboratory-Developed Tests (Journal of Namibian Studies : History Politics Culture, 2022)
The Food and Drug Administration (FDA) issued a proposed regulation in October 2022 that eliminates the ability to enforce regulations for tests developed in laboratories (LDTs). The FDA's proposal delineates a five-stage approach to implementation to start the regulation of LDTs in a manner similar to that of commercial in vitro diagnostic procedures (IVDs), including amended FDA-approved/cleared tests. This paper presents an overview of topics pertaining to the medical and public health microbiology laboratory. We believe that LDTs conducted by individual diagnostic labs recognized by Clinical Laboratory Improvement Amendments should not be subject to the same regulatory measures as commercial IVDs. If this regulation is implemented, it would have adverse effects on the diagnostic services now provided by clinical and public health labs, thereby affecting patients and their healthcare professionals. The cessation of enforcement discretion is expected to impede diagnostic innovation and diminish the availability of diagnostic testing, hence compromising health fairness. Moreover, the insufficiency of infrastructure, including both human resources and financial resources, within the FDA and diagnostic labs poses a significant hindrance to the necessary submissions for evaluation. Diagnostic labs, similar to the FDA, place a high importance on patient safety, precise clinical diagnosis, and ensuring fairness in healthcare. Given the existing lack of knowledge on the extent of the LDT landscape, we endorse the implementation of a registration procedure and a straightforward system for reporting adverse events. This will allow us to get a comprehensive understanding of the clinical applications of LDTs and any related safety issues. It is essential that regulatory rules be grounded on methodically collected facts rather than relying on anecdotes or case reports. In the context of infectious disease diagnostics, it is essential for a regulation to effectively reconcile the possible adverse effects on patient care with the practical safety hazards involved.